IMPORTANCE OF INTERACTIVE METHODS AND PEDAGOGY IN TEACHING - Niyazov Fakhriddin Buribaevich (Journals Park Publishing, 2023)
In the science of psychology teaching methods, interactive methods are based on meaningful coverage of the psychological aspects of education. Accordingly, the main concepts of teaching are developed in the teaching methodology and the use of interactive methods is based on these issues. It will be discussed about the importance of interactive methods and pedagogy in teaching.
Keywords: interactive method, teaching, pedagogy